Comparative evaluation of Indocyanine Green and 810nm Diode Laser Assisted Antimicrobial Photodynamic Therapy with 810nm Diode Laser Assisted New Attachment Procedure as adjuncts to Scaling and Root Planning in Supportive Periodontal Therapy: A Randomized Controlled Split-Mouth Clinical Trial - Sruthima NVS Gottumukkala; Sathya Valli Veluri; Gautami Subhadra Penmetsa; Ramesh KSV; Mohan Kumar Pasupuleti; Dinesh Gera; Sravanthi Vundavalli (University Library System, University of Pittsburgh, 2024)
BACKGROUND: Minimally invasive nonsurgical management of recurrent periodontal pockets remains the most viable option during supportive periodontal therapy (SPT), but with inconclusive results. The purpose of this study is to evaluate and compare the adjunctive use of Indocyanine green (ICG) and 810nm Diode laser assisted photodynamic therapy (IG-PDT) with 810nm Diode laser assisted new attachment procedure (LANAP) in the management of persistent pockets in SPT. MATERIALS AND METHODS: This single blinded randomized controlled split mouth clinical trial included 20 participants with at least two adjacent teeth with PPD ≥5mm and Clinical attachment level (CAL) ≥3mm in the contralateral quadrants. IG-PDT group received application of 5mg/ml solution of ICG for one minute followed by 810±10nm diode laser with 1W power density. LANAP group received 810±10nm diode laser application at 3W power density with 100ms and 650ms pulse duration at two consecutive passes. Clinical parameters i.e., Plaque index (PI), Gingival index (GI), PPD, CAL gain were recorded at baseline, 3 and 6 months. Landry's Healing index was assessed on the 7th day and 1 month postoperatively. Patient comfort was assessed using Visual Analog Scale (VAS) immediate post-operatively. RESULTS: Student t test and repeated measures of ANOVA were used for statistical analysis. Both site level and patient level assessments of clinical parameters showed improvement in clinical parameters in both groups. However, IG-PDT group showed significantly greater improvements in PPD (<0.001) and CAL (<0.001) at 3 and 6 months evaluation. IG-PDT showed better healing (P-0.03) at 7th post-operative day. However, LANAP showed less discomfort (2.40±0.50) compared to IG-PDT group (3.20±0.61). CONCLUSION: IG-PDT is shown to provide better clinical outcomes compared to LANAP in management of patients under SPT.